PROTOTIPE HAND-GEOMETRY SEBAGAI SISTEM VERIFIKASI - Rizal Tjut Adek (Teknik Informatika Universitas Malikussaleh, 2012)
Geometric measurements of the human hand have been used for identity authentication in a number of commercial systems. In this project we have developed a prototype hand geometry-based verification system and analyzed it's performance. We have demonstrated the practical utility of this system by designing an application that uses hand geometry as opposed to password for restricting access to a web site. We present our preliminary verification results based on hand measurements of 50 individuals captured over a period of time.